Distinct phenotypes of speech and voice disorders in Parkinson's disease after subthalamic nucleus deep brain stimulation. Issue 8 (3rd October 2014) - Tsuboi, Takashi; Watanabe, Hirohisa; Tanaka, Yasuhiro; Ohdake, Reiko; Yoneyama, Noritaka; Hara, Kazuhiro; Nakamura, Ryoichi; Watanabe, Hazuki; Senda, Jo; Atsuta, Naoki; Ito, Mizuki; Hirayama, Masaaki; et al.
Abstract : Objectives: To elucidate the phenotypes and pathophysiology of speech and voice disorders in Parkinson's disease (PD) with subthalamic nucleus deep brain stimulation (STN-DBS). Methods: We conducted a cross-sectional study on 76 PD patients treated with bilateral STN-DBS (PD-DBS) and 33 medically treated PD patients (PD-Med). Speech and voice functions, electrode positions, motor function and cognitive function were comprehensively assessed. Moreover, speech and voice functions were compared between the on-stimulation and off-stimulation conditions in 42 PD-DBS patients. Results: Speech and voice disorders in PD-DBS patients were significantly worse than those in PD-Med patients. Factor analysis and subsequent cluster analysis classified PD-DBS patients into five clusters: relatively good speech and voice function type, 25%; stuttering type, 24%; breathy voice type, 16%; strained voice type, 18%; and spastic dysarthria type, 17%. STN-DBS ameliorated voice tremor or low volume; however, it deteriorated the overall speech intelligibility in most patients. Breathy voice did not show significant changes and stuttering exhibited slight improvement after stopping stimulation. In contrast, patients with strained voice type or spastic dysarthria type showed a greater improvement after stopping stimulation. Spastic dysarthria type patients showed speech disorders similar to spastic dysarthria, which is associated with bilateral upper motor neuron involvement. Strained voice type and spastic dysarthria type appeared to be related to current diffusion to the corticobulbar fibres. Conclusions: Stuttering and breathy voice can be aggravated by STN-DBS, but are mainly due to aging or PD itself. Strained voice and spastic dysarthria are considered corticobulbar side effects.